Examination of the Continuity of Babel and Ishtar Hotels through Management Declarations and Auditor’s Opinion/an Analytical Study - Muhammad Alwan Salman; Sohad Sabih Al-Saffar (Journal of Madenat Alelem University College, 2022)
The research aims to shed light on the procedures followed by the auditor through the use of liquidity and profitability indicators, extracted from the cash flow statement, in assessing the continuity of the Babylon and Ishtar hotels. The research was built on the following hypothesis: "The liquidity and profitability indicators based on the detection of cash flows help the auditor in evaluating the financial performance of the Babylon and Ishtar hotels, subject to auditing for a period not exceeding one fiscal year." The researchers completed the practical side by studying the analysis of the financial reports of the units under study. The most prominent conclusions on the practical side were: Management declarations are audit evidence (a written statement submitted by management) that helps the auditor to reach conclusions that contribute to the formulation of his impartial technical opinion, and these decisions are also necessary information to complete an audit.. Through the declarations presented in the financial report of the hotel and tourism sector, there is no declaration showing the continuity of the units for the next (12) months, and the management of the units did not conduct an assessment of continuity despite the inclusion of the concept of continuity in the accounting rule 6. Also, the entities based on the implementation of operations. The audit (Federal Financial Supervision Bureau, and a special audit office), did not refer in the audit report to conducting assessments about continuity. The most prominent recommendations were as follows: The necessity of the auditor when auditing hotels, to put a paragraph explaining the continuity of units for the next (12) months. Shedding light on the use of financial indicators (liquidity and profitability) based on the cash flow statement because it illustrates the impact of cash flows on continuity